New pharmacological strategies to fight enveloped viruses - Wisskirchen, Karin (Trends Pharmacol Sci, 2014)
Enveloped viruses pose an important health threat because most of the persistent and many emerging viruses are enveloped. In particular, newly emerging viruses create a need to develop broad-spectrum antivirals, which usually are obtained by targeting host cell factors. Persistent viruses have developed efficient strategies to escape host immune control, and treatment options are limited. Targeting host cell factors essential for virus persistence, or immune-based therapies provide alternative approaches. In this review, we therefore focus on recent developments to generate antivirals targeting host cell factors or immune-based therapeutic approaches to fight infections with enveloped viruses.